Violacein and its antifungal activity: comments and potentialities. (22nd June 2022) - Durán, N.; Castro, G.R.; Portela, R.W.D.; Fávaro, W.J.; Durán, M.; Tasic, L.; Nakazato, G.
Abstract: Violacein is an important natural antimicrobial pigment that is mainly produced by Chromobacterium violaceum and Janthinobacterium lividum . It presents a significant range of effects against phytopathogenic and human fungi, besides being featured as having low toxicity, and by its important ecological role in protecting amphibian species and applications in dyed medical fabric. The hypothesis about violacein's action mechanisms against mucormycosis ( Rhizopus arrhizus ) and candidiasis ( Candida auris ) is herein discussed based on data available in the scientific literature. Abstract : Significance and Impact of the Study: Infections caused by fungi in the antimicrobial‐resistance Era are of great concern since many of them are comorbidities related to SARS‐CoV‐2 infection. This mini‐review is a critical analysis of violacein use, which is a natural bacterial secondary metabolite product featured by a great versatility of biological activity, a fact that turns it into a likely new strategy against phytopathogenic and human fungal infections produced by different micro‐organism species. The current manuscript aims to show violacein's potential as a new strategy against mucormycosis (caused by Rhizopus arrhizus ), an opportunist disease that may affect the respiratory tract and the skin, and candidiasis (caused by Candida auris ), a disease that has different presentations, from local lesions in the skin and mucosae, to a severe disseminated form. These two important infections must be taken into consideration in severe COVID‐19 cases. The goal was to evaluate violacein's available data, effectiveness, and safety as a new drug to be used to treat these fungal infections.